Real-Time Emulation and Simulation System of Asynchronous Motor Consumption - Sousa, Filipe (2021)
Electric power systems have been altered at the operating and planning level in the last years. Evidence of this was the liberalization of the energy market and the implementation of concepts such as smart grids and the active participation of consumers through demand response programs. The main objective of the present paper is to propose an emulation model for asynchronous motors, in the scope of dynamic measurement and control of loads, included in demand response programs. Since this type of electric motor is of upmost importance in the current consumption context, it was necessary to model consumption and evaluate its impact on the power system. The development of this paper aims to evaluate the system’s capabilities using the motor as a load, and a wind emulator. Thus, we can represent various applications (e.g. division of a house) and realize the effect of distributed generation in the operation of the electric power system.